Acoustical characteristic of empty fruit bunch (EFB) fibre with influence of sodium hydroxide treatment time and decay lifespan - Mat Wan, Lauren (2019)
Research on natural fibres has gain much interest in recent years due to the sustaibability and avaibility in which demand for green renewable reinforced composites. Natural fibres can be considered as the alternative way to replace the synthetic fibre as well as to implement the sustainability of the materials. However, the natural fibre also has its own disadvantage which is the ability to maintain the quality of absorption due to the lack of information and research on the acoustic application. Thus, in this research, the untreated and treated Empty Fruit Bunch (EFB) fibre was investigated as control unit and the standard used for sound absorption test was ISO 10534-2 and ASTM E1050-98. The EFB has undergone a chemical modification process known as alkali treatment using sodium hydroxide (NaOH). Five parameters were chosen for the alkali treatment process which is the fiber immersion time (at 1 hour until 5 hours) with fixed alkali treatment concentration of 6% NaOH. Cross sectional area of the fibre was measured using Leica stereo video analyser. The results from the test show EFB fibre gives positive value of sound absorption from mid to high frequency which is from 2000 Hz to 5000 Hz. The best sound absorption is performed by the 1 hour of treated fibre with a maximum sound absorption coefficient (α) nearly 1 at 2500 Hz and with thickness of 50 mm. The Noise Reduction Coefficient (NRC) for the 1 hour treated fibre is 0.53. As for decay lifespan, the sound absorptions performance was slightly decreased from 0.68 to 0.55 within 5 to 20 months. This result indicates that the treated EFB are highly absorptive material and it is recommended to become as a natural base for acoustical absorption material.